Dying Too Soon: Excess Mortality in Severe Mental Illness - de Mooij, Liselotte D.; Kikkert, Martijn; Theunissen, Jan; Beekman, Aartjan T.F.; de Haan, Lieuwe; Duurkoop, Pim W.R.A.; Van, Henricus L.; Dekker, Jack J.M. (Frontiers in Psychiatry, 2019)
Abstract Aims We aimed to identify baseline predictors of mortality in patients with a severe mental illness (SMI) over a six-year period and to describe mortality rates as standardised mortality ratios (SMRs). Method Medical examinations were conducted at baseline in a cohort of 322 SMI patients. SMRs were estimated after six years and an evaluation was made of the impact of a wide range of variables on survival time. Results Almost 11% of the SMI patients had died at the end of the study period. All-cause SMRs were 4.51 for all SMI patients (4.89 for men, and 3.94 for women). Natural causes accounted for 86% of excess mortality and unnatural causes for 14%. Cardiovascular disease was a major contributor to this excess mortality. Multivariate Cox regression analyses showed that premature death was associated with Western ethnicity (HR: 1.81; 95% CI: 1.60-2.05), a longer history of tobacco use (HR: 1.03; 95% CI: 1.02-1.03) and more severe symptoms of disorganisation (HR: 2.36; 95% CI: 2.21-2.52). Conclusions The high SMR and the incidence of CVD-related death in SMI patients in our study justify concern. This study underscores the urgent need for interventions to reduce excess mortality in patients with SMI.